Tumor Infiltrating Mast Cell Density in Gastric Adenocarcinoma: Association With Clinicopathological Parameters (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Tumor-infiltrating mast cells have been reported to play functional roles in the tumor microenvironment. However, controversial evidence exists regarding their impact on different cancers. The present study aimed to determine tumor-infiltrating Mast Cell Density (MCD) in gastric adenocarcinoma and its relationship with clinicopathological parameters.   Materials and methods: Fifty cases of gastric adenocarcinoma were included in this study from the Department of Surgery of Chittagong Medical College Hospital from September 2020 to June 2022. Gastrectomy specimens were sectioned and stained with routine Hematoxylin and Eosin stain. Toluidine blue stain was used to calculate MCD.Results: The mean age of the patients was 56.9±9.6 years (Range: 30-75), 56% were male, and the mean MCD was 7.13±2.85. Mean MCD was similar in patients aged